PERBANDINGAN PROFIL GLUKOSA DARAH PASIEN STROKE ISKEMIK DAN STROKE HEMORAGIK DI RSUP FATMAWATI TAHUN 2018 - Husna, Intan Rahma; Astari, Riezky Valentina; Rizkianti, Tuty (Universitas Tarumanagara, 2021)
Stroke is the death of brain cells due to lack of blood flow and oxygen to the brain by blockage or rupture of an artery. Stress hyperglycemia in acute stroke may worsen the clinical outcome and the prognosis of stroke. The purpose of this study is to find out and compare blood glucose profile between ischemic stroke and hemorrhagic stroke. This is an observational analytic cross-sectional research using consecutive sampling. Data was obtained through medical record from January to December 2018 in RSUP Fatmawati with each group of stroke consisting of 74 samples. Data was processed using SPSS 2017. Mann-Whitney test shows a significant difference in random blood glucose levels between ischemic stroke and hemorrhagic stroke (p = 0.024), with the median value of random blood glucose level during ischemic stroke is 115.50 mg / dL and hemorrhagic stroke is 136.50 mg / dL. The results also shows a significant difference in fasting blood glucose levels between ischemic stroke and hemorrhagic stroke (p = 0.042), with the median value of fasting blood glucose level for ischemic stroke is 116.50 mg / dL and hemorrhagic stroke is 125.50 mg / dL. A significant difference is also seen in 2 hours post-prandial glucose level between ischemic stroke and hemorrhagic stroke (p = 0.028), with the median value of 2 hours post-prandial glucose level of ischemic stroke is 130 mg / dL and hemorrhagic stroke is 147.50 mg / dL. Keywords: Ischemic Stroke; Hemorrhagic Stroke; Random Blood Glucose; Fasting Blood Glucose; 2 Hour Post-Prandial Blood Glucose AbstrakStroke adalah kematian sel-sel otak akibat hilangnya pasokan darah dan oksigen ke otak karena adanya hambatan atau ruptur arteri yang menuju otak. Pada stroke fase akut dapat terjadi hiperglikemia reaktif yang dapat memperburuk keluaran klinis dan prognosis stroke. Penelitian ini dilakukan untuk mengetahui dan membandingkan profil glukosa darah antara stroke iskemik dan stroke hemoragik. Penelitian ini bersifat analitik observasional dengan desain potong lintang dan pemilihan sampel consecutive sampling. Data didapat dari rekam medis periode Januari-Desember 2018 di RSUP Fatmawati dengan masing-masing kelompok stroke sebanyak 74 sampel. Pengolahan data dilakukan dengan program SPSS tahun 2017. Uji Mann-Whitney menunjukkan adanya perbedaan bermakna kadar Glukosa Darah Sewaktu antara stroke iskemik dengan stroke hemoragik (p = 0,024), dengan nilai median Glukosa Darah Sewaktu stroke iskemik adalah 115,50 mg/dL dan stroke hemoragik adalah 136,50 mg/dL. Hasil juga menunjukkan adanya perbedaan bermakna kadar Glukosa Darah Puasa antara stroke iskemik dan stroke hemoragik (p = 0,042), dengan nilai median Glukosa Darah Puasa stroke iskemik adalah 116,50 mg/dL dan stroke hemoragik adalah 125,50 mg/dL, serta adanya perbedaan bermakna kadar Glukosa Darah 2 Jam Post-Prandial antara stroke iskemik dan stroke hemoragik (p = 0,028), dengan nilai median Glukosa Darah 2 Jam Post-Prandial stroke iskemik adalah 130 mg/dL dan stroke hemoragik adalah 147,50 mg/dL.